PENGARUH KONSELING KELOMPOK TERHADAP PENGURANGAN STRES AKADEMIK SISWA KELAS X SMAN 2 SIAKHULU T.P 2014/2015 - Dena, Putri Rahma Dena Rahma; Arlizon, Raja Arlizon; Umari, Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is ‘’ Effect of Group Counseling towards the Reduction of Academic Stress of First – Year Students of Academic Year 2014/2015 at SMAN 2 Siak Hulu’’. The purposes of this research were 1) to know the description of students’ academic stress before given group counseling service, 2) to know the dynamic description of the group counseling implementation in order to reduce students’ academic stress, 3) to know the description of students’ academic stress reduction after given group counseling service, 4) to know how much the difference of students’ academic stress reduction before and after given group counseling service is,  5) to know how much the influence of group counseling towards the reduction of students’ academic stress is.  The instrument used in this research was academic stress scale. The subjects of this research were 101 first – year students of academic year 2014/2015 at SMAN 2 Siak Hulu. The sample of this research was 30 students and they were selected by simple random sampling. The description of academic stress before given group counseling was in high category (50%), medium category (46,67%), and low category (3,33%). The description of students’ academic stress reduction after given group counseling was in high category (10%), medium category (53,33%), and low category (36,67%). Based on the result of the calculation of the correlation coefficient between X1 and X2 was 0,505 and the determination coefficient (r2) was 0,255. This means that the contribution of group counseling towards the reduction of  academic stress was 25,5%. Therefore, it can be known that ttest was bigger than ttable, (7,93 > 2,000) so that Ha was accepted . So, it means that there was influence of group counseling towards the reduction of  academic stress  of first – year students of academic year 2014/2015 at SMAN 2 Siak Hulu. Keywords : Group Counseling, Academic Stress